High incidence of spring ligament laxity in ankle fractures with complete deltoid ruptures and secondary first ray instability. (March 2021) - Pasapula, Chandra; Ali, Ahmad M.S.; Kiliyanpilakkil, Biju; Hardcastle, Antonia; Koundu, Mandeep; Gharooni, Aref-Ali; Kabwama, Sylvester; Cutts, Steven
Highlights: Extent of soft tissue injury is larger than previously thought in ankle fractures. Deltoid ligament injury may include missed spring ligament injury also. Spring ligament injury leads to early first ray destabilization. Early monitoring for this wider injury zone is required. Abstract: Aims: To assess the incidence of spring ligament failure in patients who have complete deltoid ruptures. Patients and methods: The authors retrospectively analysed ankle fractures in our trauma database from January 2015 to January 2019. 61 patients who sustained ankle fractures with complete deltoid ligament ruptures based on an AP ankle radiographs with increased medial joint space were identified. 25 patients attended clinic for assessment. Of these, 5 were found to have gross planovalgus with pre-existing spring ligament laxity in the uninjured control foot and these were excluded from the analysis. 20 patients were assessed for spring ligament failure /laxity. For each patient, the uninjured foot was used as the control. Results: The TMT instability score and the lateral translation score showed statistically significant increases in the injured compared to the uninjured foot. The ratio of increase in both TMT instability and lateral translation scores (strain) in the injured versus the uninjured foot was assessed. A strong correlation (+0.62 pearson correlation coefficient) was found between the two ratios. Conclusion: All 20 patients showed increased spring ligament laxity and 19 patients showed increased TMT instability. Our results show that with complete deltoid rupture, there is likely greater disruption of the medial ligamentous structures of the foot than previously recognised. The degree of increase in the spring ligament strain also correlates with the degree of strain at the plantar TMT joint ligaments, and thus first ray instability. This finding has significant implications for the long-term assessment and management of ankle fractures involving complete deltoid disruption. Early intervention with orthotics in this cohort may prevent progressive destabilisation of the midfoot and the first ray. This evolving understanding may lead to the prospect of earlier surgical intervention to reconstitute the integrity of the spring ligament and protect the foot progressing to stage 2 AAFD.